(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
In the modern era, ensuring sustainable socio-economic development is regarded as one of the main priorities at both global and regional levels. The concept of sustainable development holds particular significance for ensuring a healthy, safe, and high standard of living for society. This development model aims, on the one hand, to preserve natural resources and, on the other, to establish a balance between human activities and the environment. The key principles of sustainable development include promoting economic growth, expanding social inclusivity, and protecting the environment. The simultaneous implementation of these principles is considered a fundamental condition for long-term and continuous progress. In this context, the study of the impact of agriculture on socio-economic development gains particular relevance. Agriculture plays a vital role not only in ensuring food security but also in increasing employment in rural regions. At the same time, the application of modern and innovative methods in this sector enables more efficient use of resources, enhances productivity, and contributes to maintaining ecological balance. Sustainable agricultural systems are not limited to the optimal management of natural resources such as land and water; they also play an important role in increasing economic activity and innovation potential in rural areas, promoting rural development, expanding social infrastructure, and strengthening the capacity to adapt to climate change. Moreover, the implementation of modern and innovative approaches in agriculture significantly contributes to both the efficient use of natural resources and the overall economic growth. For this reason, the application and improvement of sustainable development models in agriculture is considered one of the key directions of contemporary research.